Time-lapse analysis of retinal differentiation - Poggi, Lucia (Current opinion in cell biology, 2005)
The availability of new vital markers and the improvements in time-lapse video microscopy have increased our ability to observe developmental events in the retina while they are happening. Using this approach, advances have been made in the understanding of important issues such as how division patterns relate to cell fate determination, how post-mitotic progenitors reach their correct retinal layers, and finally, how retinal ganglion cell axons navigate out of the retina and to their final targets in the midbrain.1Lucia Poggi and Flavio Zolessi contributed equally to the manuscript.